Mothers' perceptions and attitudes about HPV vaccination initiation among 9- and 10-year-olds - Racquel E. Kohler; Rachel B. Wagner; Katherine Careaga; Rula Btoush; Kathryn Greene; Leslie Kantor (Taylor & Francis Group, 2023)
ABSTRACTHPV vaccination has potential to prevent 90% of HPV-associated cancers. The Advisory Committee on Immunization Practices recommends HPV vaccination for 11- and 12-year-olds, but vaccine initiation can start at age 9. The purpose of this study was to explore perceptions about starting HPV vaccination at a younger age to inform future interventions that promote initiation at ages 9 and 10 years. This was part of a larger study about vaccine hesitancy among racially/ethnically diverse parents of adolescents in the Greater Newark Area of New Jersey. We thematically analyzed transcripts from 16 interviews with English- and Spanish-speaking mothers who had at least one child ≤ 10 years. Analyses focused on perceptions of HPV-related disease risk, attitudes toward HPV vaccination need, and vaccine confidence specifically for 9- and 10-year-olds. Few parents with young adolescents reported receiving vaccination recommendations, and only one reported series initiation before age 11. Mothers' hesitation about younger HPV vaccination initiation revolved around: 1) low perceived necessity among English-speaking mothers due to young adolescents not being sexually active, 2) concerns about potential side effects associated with vaccinating prepubescent adolescents, and 3) a desire for adolescents to be old enough to provide assent. Participants were not opposed to younger initiation but wanted and relied on pediatricians to inform them about vaccination for younger adolescents. These findings suggest mothers are willing to vaccinate at younger ages after clear provider recommendations. Equipping providers with evidence about vaccine safety and cancer prevention communication strategies may promote initiation and timely completion at younger ages.